BEYOND COMPUTER LITERACY: TECHNOLOGY INTEGRATION AND CURRICULUM TRANSFORMATION. - SAFAR, AMMAR H.; ALKHEZZI, FAHAD A. (College Student Journal)
Personal computers, the Internet. smartphones, and other forms of information and communication technology (ICT) have changed our world, our job, our personal lives, as well as how we manage our knowledge and time effectively and efficiently. Research findings in the past decades have acknowledged and affirmed that the content the ICT medium carries is as important as the ICT medium itself. These studies also added a third constituent to the structure of ICT usage and integration; that is the pedagogical approach of teaching and learning. One of the modern ICT trends of organizations involves the incorporation and integration of a blended approach of teaching and learning; which combines the traditional face-to-face instructor-led method with ICT-based online teaching and learning environment. This quasi-experimental research study was deployed to evaluate and identify the effect and usefulness of a blended pedagogical approach of teaching and learning on students' academic achievement, motivation, and attitudes. A total of 128 (i.e., 64 experimental group and 64 control group) undergraduate students in the College of Education (COE) at Kuwait University (KU) participated in this study. The results revealed that the students enrolled in the experimental group were significantly outscoring their counterparts in the control group. They submitted projects with better quality; earned higher final grades; attended more online training courses; took more ICDL tests; and the majority attended all classes. These findings imply that the potential of a blended approach of teaching and learning is endless. It can produce robust teaching and learning environments and experiences, it can also reveal that teaching and learning with such method or strategy, while integrating and incorporating ICT tools, can be fun.